A comprehensive review of the botany, ethnopharmacology, biochemistry, pharmacology, pharmacokinetics and toxicity of Filifolium sibiricum (L.)Kitam - Shaowa Lv; Qian Qiu; Qiuhong Wang; Haixue Kuang (BMC, 2021)
Abstract Filifolium sibiricum (L.)Kitam (F. sibiricum), a compositae plant, is especially used to inhibit drug-resistant bacteria in folk medicine. Modern pharmacological studies also confirmed a variety of pharmacological properties about sedative activities, antibacterial activity, anti-inflammatory activity, analgesic activities, antitussive and asthma relieving. In this paper, the research progress of F. sibiricum in botany, ethnopharmacology, phytochemistry, pharmacology, pharmacokinetics and toxicology was reviewed. Prospects for future investigation and application of this herb were also discussed. Information on F. sibiricum was gathered from various sources, including books on traditional Chinese herbal medicine and scientific databases such as PubMed, Google Scholar, Science Direct, Baidu Scholar, CNKI and other professional websites. The results indicate that ~ 66 chemical compounds were isolated and identified from F. sibiricum. Among them, flavonoids are generally considered to be the main bioactive and characteristic ingredients. F. sibiricum is a traditional Chinese medicine with pharmacological activities such as the immune system, nervous system, respiratory system and cardiovascular and cerebrovascular systems. Most importantly, we should concentrate on developing new drugs related to F. sibiricum, so as to exert greater potential for treatment.